Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2009
DOI: 10.1080/00986280902739636
|View full text |Cite
|
Sign up to set email alerts
|

The Power of Situations: Jonestown and the Fundamental Attribution Error

Abstract: The fundamental attribution error (FAE) is the tendency to overestimate dispositional and underestimate situational causes for others' behavior (Ross, 1977). Undergraduate students (N = 155) explained the causes of a person's "bad day." The experimental group completed responses after viewing a documentary on Jonestown and discussing situational factors in that environment; 3 other groups completed responses after a research methods lecture (control) or lectures on the FAE. Participants exposed to the film ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
13
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 23 publications
(22 reference statements)
0
13
0
Order By: Relevance
“…To measure participants' susceptibility to FAE (i.e., the degree to which individuals rely on dispositional vs. situational attributes), we began with the ''Ron's Bad Day'' scenario from Riggio and Garcia (2009), and created additional clone scenarios, which included items depicting both positive and negative events. Each vignette presented a short, distinct, narrative in which the central character either suffered negative consequences from a series of poor choices and unfortunate circumstances, or enjoyed positive outcomes from superior choices and fortuitous circumstances.…”
Section: Faementioning
confidence: 99%
“…To measure participants' susceptibility to FAE (i.e., the degree to which individuals rely on dispositional vs. situational attributes), we began with the ''Ron's Bad Day'' scenario from Riggio and Garcia (2009), and created additional clone scenarios, which included items depicting both positive and negative events. Each vignette presented a short, distinct, narrative in which the central character either suffered negative consequences from a series of poor choices and unfortunate circumstances, or enjoyed positive outcomes from superior choices and fortuitous circumstances.…”
Section: Faementioning
confidence: 99%
“…However, two studies reported that such education at least reduced dispositional attributions (Chen et al, 1997;Riggio & Garcia, 2009). Chen et al (1997) measured the FAE in master's students in counselling as they assessed client problems from videotaped cases.…”
Section: Previous Fae Education Researchmentioning
confidence: 99%
“…Using undergraduates, Riggio and Garcia (2009) tested a more long-term effect of a 25-minute FAE lecture. In comparison with a control, the lecture reduced undergraduates' dispositional attributions in explaining a target's 'bad day', both 2 and 14 days later.…”
Section: Previous Fae Education Researchmentioning
confidence: 99%
See 2 more Smart Citations